2011
DOI: 10.1007/s11418-010-0505-7
|View full text |Cite
|
Sign up to set email alerts
|

Methyl galbanate, a novel inhibitor of nitric oxide production in mouse macrophage RAW264.7 cells

Abstract: It is well known that inflammation is associated with various neurodegenerative diseases, such as Parkinson's disease and Alzheimer's disease. An inflammatory mediator, nitric oxide (NO), is produced by inducible NO synthase (iNOS) in microglia and seems to be one of the possible causes of neurodegeneration. Several natural and synthetic compounds which exert anti-inflammatory effects by inhibiting NO production have been reported to date. The aim of this work was to investigate whether any of the 6 terpenoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 21 publications
1
30
1
Order By: Relevance
“…Methyl galbanate 10 mM GA showed no effect on NO production; Methyl galbanate significantly inhibited NO production; Methyl galbanate exerts its anti-inflammatory effect by inhibiting iNOS mRNA expression (Kohno et al, 2011) Figure 2. Timeline of the proposed structures of galbanic acid by date.…”
Section: Ga 10 MMmentioning
confidence: 99%
See 1 more Smart Citation
“…Methyl galbanate 10 mM GA showed no effect on NO production; Methyl galbanate significantly inhibited NO production; Methyl galbanate exerts its anti-inflammatory effect by inhibiting iNOS mRNA expression (Kohno et al, 2011) Figure 2. Timeline of the proposed structures of galbanic acid by date.…”
Section: Ga 10 MMmentioning
confidence: 99%
“…In addition, methyl galbanate slightly attenuated COX-2 mRNA expression. Their findings revealed that the membrane permeability of methyl galbanate was higher than that of GA due to the presence of a hydrophobic methyl-esterified group (Kohno et al, 2011).…”
Section: Miscellaneous Activitiesmentioning
confidence: 99%
“…GBA is a lipophilic sesquiterpene coumarin and possesses different approved pharmaceutical activities. Synergism effect of GBA with penicillin G and cephalexin (Shahverdi et al, 2007), erythrocyte aggregation inhibitory properties (Mansurov & Martirosov, 1988), hepatoprotective effects through liver redox potential improving (Syrov et al, 1990), inhibition of the nitric oxide (NO) production (Kohno et al, 2011), down-regulation of androgen receptors abundance in the prostate gland (Zhang et al, 2012), anti-leishmanial activity (Iranshahi et al, 2007), and farnesyl-transferase inhibition (Cha et al, 2011) have reported for the compound.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that iNOS and NO are involved in inflammation, neurodegeneration, and NP and one of underlying mechanism of UMB is iNOS inhibitory effects. [19][20][21] UMB (0.01 mM) with morphine (1 mg/kg) potentiated morphine antinociceptive effects. UMB shows its antinociceptive effcts partly via µ receptors stimulation.…”
mentioning
confidence: 95%